2023
DOI: 10.1021/acsestengg.2c00279
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Mechanisms of Periodate-Based Pretreatment in Enhancing Short-Chain Fatty Acids from Waste Activated Sludge

Abstract: Resource recovery in the form of short-chain fatty acids (SCFAs) from waste activated sludge (WAS) is usually limited due to the quantity and quality of SCFAs. To mitigate these restrictions, this study provides a novel method by using periodate (PI) pretreatment. With an increase in the PI concentration from 0 to 50 mg/g total solids (TS), the SCFA yield increased from 1486 to 3109 mg COD/L and acetic acid production was enhanced by more than twice. Further increase of PI had an adverse effect on SCFA product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Foughal et al used Aspergillus niger to eliminate bacteria and pathogens in food waste, thereby accelerating the production of organic fertilizers [42]. Du et al and Li et al found that many fast foods contain a significant number of additives, which can inhibit anaerobic digestion, leading to a reduction in methane production [43]. However, when compared to lower additive levels, the production of organic acids can be increased by 12.5% [16].…”
Section: Food Wastementioning
confidence: 99%
“…Foughal et al used Aspergillus niger to eliminate bacteria and pathogens in food waste, thereby accelerating the production of organic fertilizers [42]. Du et al and Li et al found that many fast foods contain a significant number of additives, which can inhibit anaerobic digestion, leading to a reduction in methane production [43]. However, when compared to lower additive levels, the production of organic acids can be increased by 12.5% [16].…”
Section: Food Wastementioning
confidence: 99%